School teachers’ perception on the role of the school library media specialist: A case study / Jasveen Kaur Berdewa Singh - Jasveen Kaur , Berdewa Singh (2019)
Over the years, the School Library Media Centre has evolved to be an integral part of the school system, from curriculum development to resources collection and development, as well as teaching and learning advancements. The school library media collection and other information resources on their own cannot prove successful to fulfil the schools’ goals which are contained in the mission statement. Therefore, the media specialist or school librarian has been perceived as the bridge that links both information resources, media collection, teachers and students in the school. The position and job responsibilities has placed a lot of demand on the media specialist from both teachers, school management and other staff in the school. These responsibilities are divided into several roles that are expected of the media specialist to perform, from curriculum specialist, technologist, to teaching collaborator and so on. This study is an investigation of school teachers’ perception on the role of the School Library Media Specialist. It uses the SMJK Pei Yuan, Kampar district, Perak, Malaysia as the research setting. The study is guided by five specific objectives: (i) To explore the perception of teachers about the School Library Media Specialists’ awareness of the curriculum; (ii) To explore the perception of the teachers on the role of the School Library Media Specialist as an instructional partner; (iii)To explore the perception of the teachers on the role of the School Library Media Specialist as an information literacy program administration; (iv) To explore the perception of the teachers on the role of the School Library Media Specialist as an information specialist. The study also aims to investigate if there is a difference in perception of the teachers of the role of the School Library Media Specialist based on their years of teaching experience. This study uses a quantitative approach with survey as the research method. It employs a Questionnaire as the instrument for data collection. All teachers of SMJK Pei Yuan Kampar, Perak served as the population for this study. The data is analysed descriptively, and results are presented using table of frequency counts and percentages. Findings reveal that most respondents perceive that the School Library Media Specialist has achieved the roles to a great or to a very great extent. These include roles as an instructional partner, information literacy programme administrator, Information specialist and their level of curriculum awareness. The test of mean differences in teachers’ perception of the role of the media specialist according to experience revealed that the teachers who have worked for 16 years and above and those between 11-15 years had higher level of perception and it was significantly different from from those with lesser years of experience. Finally, this study has revealed that teachers are aware of the School Library Media Specialist’s role in supporting the successful academic activities in the school. Also, media specialists’ collaboration with teachers in teaching, learning, resources and technology implementation is central to the fulfilment of the school’s mission and goals. Therefore, this study has contributed to the existing body of knowledge regarding the vital roles and perceptions of teachers of the roles of the school library media specialist.